Systemic inflammation early after kidney transplantation is associated with long-term graft loss: a cohort study - Heldal, Torbjørn F.; Åsberg, Anders; Ueland, Thor; Reisæter, Anna V.; Pischke, Søren E.; Mollnes, Tom E.; Aukrust, Pål; Reinholt, Finn; Hartmann, Anders; Heldal, Kristian; Jenssen, Trond G. (Frontiers in Immunology, 2023)
Background: Early graft loss following kidney transplantation is mainly a result of acute rejection or surgical complications, while long-term kidney allograft loss is more complex. We examined the association between systemic inflammation early after kidney transplantation and long-term graft loss, as well as correlations between systemic inflammation scores and inflammatory findings in biopsies six weeks and one year after kidney transplantation. Methods: We measured 21 inflammatory biomarkers ten weeks after transplantation in 699 patients who were transplanted between 2009 and 2012 in Oslo University Hospital, Rikshospitalet, Norway. Low-grade inflammation was assessed with predefined inflammation scores based on specific biomarkers: one overall inflammation score and five pathway-specific scores. Surveillance or indication biopsies were performed in all patients six weeks after transplantation. The scores were tested in Cox regression models. Results: Median follow-up time was 9.1 years (interquartile range 7.6-10.7 years). During the study period there were 84 (12.2 %) death-censored graft losses. The overall inflammation score was associated with long-term kidney graft loss both when assessed as a continuous variable (hazard ratio 1.03, 95% CI 1.01-1.06, P = 0.005), and as a categorical variable (4th quartile: hazard ratio 3.19, 95% CI 1.43-7.10, P = 0.005). In the pathway-specific analyses, fibrogenesis activity and vascular inflammation stood out. The vascular inflammation score was associated with inflammation in biopsies six weeks and one year after transplantation, while the fibrinogenesis score was associated with interstitial fibrosis and tubular atrophy. Conclusion: In conclusion, a systemic inflammatory environment early after kidney transplantation was associated with biopsy-confirmed kidney graft pathology and long-term kidney graft loss. The systemic vascular inflammation score correlated with inflammatory findings in biopsies six weeks and one year after transplantation.